2022
DOI: 10.2147/prbm.s352279
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Functioning in the Context of Health Behaviors During the COVID-19 Pandemic in Health Sciences Students: The Polish Case

Abstract: Purpose The fear for health, uncertainty, loss of freedom, boredom, and frustration accompanying the COVID-19 pandemic caused mental health burdens. Young people are particularly at a risk of emotional functioning problems. The aim of this manuscript was to verify the relationships between health behaviors and emotional functioning in health sciences students during the third wave of the COVID-19 pandemic in Poland. Patients and Methods The study group comprised 493 Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Similarly, social support and adequate sleep have been found to protect against trauma among first responders (Feldman et al, 2021). Dębska-Janus et al (2022) found that undertaking regular healthy behaviors, such as a positive mental attitude, healthy eating, following preventive health recommendations, and pro-health activities such as adequate sleep, recreation, and physical activity, decreased the odds of developing severe symptoms of anxiety, depression, and stress in health sciences students during the COVID-19 pandemic.…”
Section: Theory Of Stress and Copingmentioning
confidence: 99%
“…Similarly, social support and adequate sleep have been found to protect against trauma among first responders (Feldman et al, 2021). Dębska-Janus et al (2022) found that undertaking regular healthy behaviors, such as a positive mental attitude, healthy eating, following preventive health recommendations, and pro-health activities such as adequate sleep, recreation, and physical activity, decreased the odds of developing severe symptoms of anxiety, depression, and stress in health sciences students during the COVID-19 pandemic.…”
Section: Theory Of Stress and Copingmentioning
confidence: 99%